Improved performance of perovskite light-emitting diodes with a NaCl doped PEDOT: PSS hole transport layer - Huang, Xiaokun; Bäuerle, Rainer; Scherz, Felix; Tisserant, Jean-Nicolas; Kowalsky, Wolfgang; Lovrinčić, Robert; Hernandez-Sosa, Gerardo (Journal of materials chemistry. C, Materials for optical and electronic devices, 2021)
We demonstrate a simple and effective way to enhance the performance of perovskite light-emitting diodes (PeLEDs) by utilizing an alkali halide doped PEDOT:PSS as the hole transport layer (HTL). The alkali halide (NaCl) doping helped the growth of the quasi-2D perovskite phases on top of the PEDOT:PSS, it also significantly reduced the exciton quenching in PEDOT:PSS based PeLEDs. More importantly, the doping reduced the work function of the PEDOT:PSS surface, which appropriately modulated the hole injection leading to improved charge balance. This helps to control the recombination zone inside the thin perovskite emitting layer (∼10 nm). The optimized blue-green PeLEDs with the NaCl doped PEDOT:PSS HTL showed a maximum luminance of 1487 cd m−2, current efficiency of 2.16 cd A−1 with a low turn-on voltage of 3.0 V, which are 217% and 567% higher than the PeLEDs with the pristine PEDOT:PSS layer (turn-on voltage: 3.3 V), respectively.
Gesehen am 02.06.2021